RANCANG BANGUN APLIKASI LEARNING MANAJEMEN SYSTEM BERBASIS WEBSITE PADA SMP NEGERI 19 MALUKU TENGAH - Josseano Amakora Koli Parera; Caryl Alyona; Mey Chintya Yesaya (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Advances in information technology have encouraged SMP Negeri 19, Central Maluku, to integrate digital-based learning systems to improve the quality of the teaching and learning process. This research aims to design and implement a website-based learning management system (LMS) at the junior high school level as a supporting medium for online and blended learning. The research method used is the Waterfall method, with stages including needs analysis, system design, development, implementation, and testing.The developed system's main features include learning material management, uploading and downloading assignments, online exams, and student learning outcome reports. The system was tested through a pilot study with teachers and students at SMP Negeri 19, Central Maluku, to determine the feasibility and effectiveness of LMS use. The results showed that the LMS increased student engagement in the learning process, facilitated teacher material management and assessment, and improved academic administration efficiency.Based on the evaluation results, the system was deemed suitable for use as a learning medium at SMP Negeri 19, Central Maluku, and could support the ongoing digital transformation of education. Keywords: Learning Management System, Website, Design, and Build